Um estudo sobre a sustentabilidade financeira do programa seguro-desemprego no Brasil (2000-2022) à luz da interpretação pós-keynesiana - Araújo, Leina Iade (2024)
The present dissertation aims to study the financial sustainability of the unemployment insurance program in Brazil based on its ability to adapt to the country's socioeconomic changes between the years 2000 and 2022. To analyze this topic, the theoretical approach of the Post-Keynesian School was chosen. In this way, the historical evolution of the unemployment insurance program in Brazil and its operation from 2000 to 2022 is analyzed. The core of this investigation starts from the increase in insurance expenses, the amount paid with the benefit between 2008 and 2015 increased by around 140%. This led to the investigation of the long-term relationship between revenues from the Workers' Support Fund (FAT), unemployment insurance expenses and macroeconomic variables GDP and the unemployment rate. To this end, the econometric methodology of a vector error correction model (VECM) was used. The results indicated that the variables included in the model play a significant role in explaining variations in FAT revenue in the long term. This empirical evidence strengthens post-Keynesian interpretations about the need for stability in employment policies and the economy as a whole for the sustainability of the social protection system